2016
DOI: 10.1007/s00464-016-4843-8
|View full text |Cite
|
Sign up to set email alerts
|

Effectivity of laparoscopic inguinal hernia repair (TAPP) in daily clinical practice: early and long-term result

Abstract: Laparoscopic repair can be applied to all types of inguinal hernia as a daily routine procedure with low rates of recurrences and chronic pain. Limiting factor may be extensive adhesions after previous major surgery in the lower abdomen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 36 publications
0
23
0
5
Order By: Relevance
“…This can lead to the occurrence of perioperative complications and delay the return to daily life. Generally, the risk assessment of LHS was based on patient's age, underlying diseases, type of hernia, size of hernia orifice, ASA class etc; however, no studies investigated the association between patient's PS and the incidence of perioperative complications. This study for the first time showed that poor PS is an independent predictive factor of perioperative complications after TAPP.…”
Section: Discussionmentioning
confidence: 99%
“…This can lead to the occurrence of perioperative complications and delay the return to daily life. Generally, the risk assessment of LHS was based on patient's age, underlying diseases, type of hernia, size of hernia orifice, ASA class etc; however, no studies investigated the association between patient's PS and the incidence of perioperative complications. This study for the first time showed that poor PS is an independent predictive factor of perioperative complications after TAPP.…”
Section: Discussionmentioning
confidence: 99%
“…9 While it is known that some patients undergoing open repair experience postoperative chronic pain for several months, chronic pain after laparoscopic repair has not been well evaluated. 10,11 Although Nienhuijs et al reported that less chronic pain occurred after laparoscopic repair compared to that for open repair, the observation period was relatively short (3 months) for the evaluation of chronic pain. 12 Moreover, few trials have been conducted evaluating the frequency or degree of chronic pain after laparoscopic repair.…”
Section: Introductionmentioning
confidence: 99%
“…The use of alloplastic materials has become the standard procedure in inguinal hernia surgery [1][2][3][4][5][6]. Hernia surgery is one of the most common visceral operations and thus of great medical and economic importance.…”
Section: Introductionmentioning
confidence: 99%
“…Hernia surgery is one of the most common visceral operations and thus of great medical and economic importance. Many publications have shown that there are advantages in the early postoperative outcome and lower recurrence rate when using techniques with mesh implantation compared with mesh-free inguinal hernia repair [1][2][3][4][5][6]. Therefore, inguinal hernia repair with mesh has become the standard in the last 20 years.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation